2020
DOI: 10.1158/2159-8290.cd-19-1130
|View full text |Cite
|
Sign up to set email alerts
|

Acalabrutinib plus Obinutuzumab in Treatment-Naïve and Relapsed/Refractory Chronic Lymphocytic Leukemia

Abstract: Acalabrutinib is a selective irreversible Bruton tyrosine kinase (BTK) inhibitor that does not affect IL2-associated tyrosine kinase or antibody-dependent cellular cytotoxicity, making it an attractive candidate for combination therapy with anti-CD20 antibodies. We investigated acalabrutinib plus obinutuzumab in a phase Ib/II study (NCT02296918) of patients with treatment-naïve or relapsed/refractory chronic lymphocytic leukemia (CLL). Nineteen treatment-naïve and 26 relapsed/refractory patients were treated w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
54
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(60 citation statements)
references
References 32 publications
3
54
0
3
Order By: Relevance
“…72 At a median follow-up of 39 months in treatment-naive patients and 42 months in patients with R/R CLL, the ORRs were 95% and 92%, respectively. 72 At 36 months, 94% of treatment-naive patients and 88% of patients with R/R CLL were progression-free. ELEVATE-TN assessed the efficacy and safety of obinutuzumab in combination with acalabrutinib in comparison with acalabrutinib monotherapy and with obinutuzumab plus chlorambucil (n = 535 total; n = 179, 179 and 177, respectively).…”
Section: Clinical Studies Of Acalabrutinib In Patients With MCLmentioning
confidence: 93%
“…72 At a median follow-up of 39 months in treatment-naive patients and 42 months in patients with R/R CLL, the ORRs were 95% and 92%, respectively. 72 At 36 months, 94% of treatment-naive patients and 88% of patients with R/R CLL were progression-free. ELEVATE-TN assessed the efficacy and safety of obinutuzumab in combination with acalabrutinib in comparison with acalabrutinib monotherapy and with obinutuzumab plus chlorambucil (n = 535 total; n = 179, 179 and 177, respectively).…”
Section: Clinical Studies Of Acalabrutinib In Patients With MCLmentioning
confidence: 93%
“…While a small percentage of CLL cases will never progress from this indolent disease phase, most patients will maintain a watchful waiting period until worsening cytopenias or disease symptoms emerge, upon which treatment begins. Recent advances in treatment of patients with CLL have dramatically improved patient outcomes, prompted by innovations in drugs targeting B-cell receptor (BCR) signaling pathways including Bruton's tyrosine kinase (BTK) [3][4][5][6][7][8] or phosphoinositide 3-kinases (PI3K) [9][10][11][12][13], or disruption of the B-cell lymphoma 2 (BCL2) [14][15][16][17] inhibitor of apoptosis, among others [18]. Each class of drug yields extended remissions with variable time periods of treatment ranging from intermittent to continuous.…”
Section: Introductionmentioning
confidence: 99%
“…Given the success of ibrutinib, several clinical trials were directly conducted both in naive and R/R CLL/SLL patients to determine whether the second-generation irreversible BTK inhibitors acalabrutinib and zanubrutinib would be effective. Byrd, Awan, and Woyach et al reported that acalabrutinib showed an approximate ORR of 90% in ibrutinib-treated or not treated, naive or R/R CLL/SLL, although the longest follow-up time was only 41 months and data maturity requires time [77][78][79][80]. These interim analyses demonstrated favourable safety and durability of the response with acalabrutinib, leading to FDA approval of acalabrutinib as a treatment for R/R CLL/SLL in 2019.…”
Section: Clinical Development Of Btk Inhibitors In Cll/sllmentioning
confidence: 99%